2017
DOI: 10.1039/c7cp02691a
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule probing of amyloid nano-ensembles using the polymer nanoarray approach

Abstract: Soluble amyloid-beta (Aβ) oligomers are the prime causitive agents of cognitive deficits during early stages of Alzheimer’s disease (AD). The transient nature of the oligomers makes them difficult to characterize by traditional techniques, suggesting that advanced approaches are necessary. Previously developed fluorescence-based tethered approach for probing intermolecular interactions (TAPIN) and AFM-based single-molecule force spectroscopy are capable of probing dimers of Aβ peptides. In this paper, a novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…AFM force spectroscopy studies revealed novel properties of transiently formed amyloid dimers, this method was limited to probing of dimers. To extend the force spectroscopy technique to oligomers longer than dimers, we developed an approach in which Aβ(14-23) trimers and tetramers were probed with the use of preformed Aβ(14-23) dimers (Maity et al, 2017b). The dimers were assembled using the recently developed flexible nano array (FNA)-oligomer approach in which monomers are tethered inside a flexible polymer, thereby keeping the monomers in close proximity due to the high flexibility of the FNA scaffold (Krasnoslobodtsev et al, 2015;Maity et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…AFM force spectroscopy studies revealed novel properties of transiently formed amyloid dimers, this method was limited to probing of dimers. To extend the force spectroscopy technique to oligomers longer than dimers, we developed an approach in which Aβ(14-23) trimers and tetramers were probed with the use of preformed Aβ(14-23) dimers (Maity et al, 2017b). The dimers were assembled using the recently developed flexible nano array (FNA)-oligomer approach in which monomers are tethered inside a flexible polymer, thereby keeping the monomers in close proximity due to the high flexibility of the FNA scaffold (Krasnoslobodtsev et al, 2015;Maity et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Additional analysis of the rupture process, as performed in [12] for Aβ(14-23) dimer, can reveal interesting properties of dimer assembly. The FNA approach was critical in probing interactions between Aβ(14-23) dimer and monomer and dimer-dimer interactions [11]. This suggests that FNA can be used to probe higher order oligomers with three or more conjugated monomer units.…”
Section: Methodsmentioning
confidence: 99%
“…We have recently introduced an approach that allowed us to characterize dimers formed by different amyloidogenic polypeptides [10]. The use of a flexible polymeric platform that contained the assembled oligomers allowed us to probe oligomers larger than dimers [11]. The flexible polymer is synthesized from the non-nucleoside PA spacers using a commercial DNA synthesizer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For experiments that extend a single protein (mechanical unfolding), some of these problems have been addressed by site-specific immobilization onto passivated surfaces 25 or by insertion of the protein of interest into a mechanically strong protein within a protein concatemer. 26 For protein-protein interaction studies, Lyubchenko and coworkers have developed a "flexible nanoarray" method 27,28 whereby pairs of aggregation-prone peptides are tethered onto an extensible linker at a defined separation, allowing dimerization events to be analyzed. 27 Extending the tether using the AFM allows dissociation to be measured away from the surface.…”
Section: Introductionmentioning
confidence: 99%